Evaluation of the knowledge level and practices of family physicians about newborn follow-up: survey-based observation and comparison of 220 physicians in Ankara, Turkey - Guler Sonmez, Tugba; Ugras Tiryaki, Ebru; Bozan, Mehmet Bugra; Altuntas, Nilgun (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the management-related practices and knowledge levels of family physicians about newborns, and to identify the factors that affected their practices and knowledge levels. Method: The descriptive study was conducted at Ankara Yildirim Beyazit University Yenimahalle Training and Research Hospital, Ankara, Turkiye from August to November 2021, and comprised general practitioner family physicians, family medicine specialists and family medicine residents. Data was collected using a 26-item e-survey prepared on Google Forms that covered demographic and occupational information, including neonatal practices and knowledge regarding newborn follow-up. Data was analysed using SPSS 25. Results: Of the 220 subjects, 112(50.91%) were males and 108(49.09%) were females. The overall media age was 37 years (interquartile range: 32-43 years). There were 114(51.82%) specialists, 74(33.64%) general practitioners and 32(14.55%) residents. Professional experience was >10 years in 113(51.36%) cases. Knowledge scores were not significantly different among the healthcare providers (p>0.05). The residents had higher scores for re-lactation knowledge compared to the general practitioners (p=0.009). The specialists and residents were more likely to recommend attending breastfeeding polyclinics, to completely undress the baby during examination, and to perform depression screening in mothers compared to the general practitioners (p<0.05). Conclusion: Despite having largely similar knowledge scores, family medicine specials and residents appeared to demonstrate relatively better practices compared to the general practitioners. Key Words: Newborn management, Breastfeeding, Family physicians, Knowledge level.